Linkage and Genetic Map Length in TETRAHYMENA THERMOPHILA - McCoy, J. Wynne (1977)
The genetic map of T. thermophila has been extended with tests of over 170 marker combinations. Three linkage groups have been identified, in addition to several apparent linkages which are seen only when certain strains are used. A sampling argument was developed to estimate the total genetic map length from the observed fraction of marker combinations showing linkage. If the strain-dependent linkages are actually due to structural heterozygosity, the total map length is estimated at about 1,200 cM.